2001
DOI: 10.1182/blood.v97.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding to integrin αvβ3requires tyrosine 178 in the αv subunit

Abstract: Integrin ␣ v ␤ 3 has been implicated in angiogenesis and other biological processes. However, the ligand-binding sites in ␣ v , a non-I-domain ␣ subunit, remain to be identified. Recently in ␣ IIb , the other partner of the ␤ 3 subunit, several discontinuous residues important for ligand binding were identified in the predicted loops between repeats 2 and 3 (W3 4-1 loop) and within repeat 3 (W3 2-3 loop). Based on these findings, alaninescanning mutagenesis in 293 cells was used to investigate the role of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
1
28
0
2
Order By: Relevance
“…45 In addition, we recently clarified the difference in the ligand binding sites between ␣IIb and ␣v. 34 In this study, we newly demonstrate that Ser162Leu and Arg216Gln mutations show a different effect on ligand binding between 2 ␤ 3 integrins. Consistent with the reports by Newman's group, 32,33 we showed that Ser162Leu and Arg216Gln mutations impaired the stability of the complex between ␣IIb and ␤ 3 , as evidenced by the fact that the binding of complex-specific MoAb AP2 was markedly impaired compared with that of the ␣IIb-specific MoAb TP80.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…45 In addition, we recently clarified the difference in the ligand binding sites between ␣IIb and ␣v. 34 In this study, we newly demonstrate that Ser162Leu and Arg216Gln mutations show a different effect on ligand binding between 2 ␤ 3 integrins. Consistent with the reports by Newman's group, 32,33 we showed that Ser162Leu and Arg216Gln mutations impaired the stability of the complex between ␣IIb and ␤ 3 , as evidenced by the fact that the binding of complex-specific MoAb AP2 was markedly impaired compared with that of the ␣IIb-specific MoAb TP80.…”
Section: Discussionmentioning
confidence: 98%
“…However, our previous study showed that the expression of these endogenous ␣v integrins appeared to be low compared with exogenous ␣ v ␤ 3 . 34 Indeed, the Leu117Trp ␤ 3 mutation severely impaired the expression of ␣v subunits as well as ␣ v ␤ 3 , suggesting that the bulk of expressed ␣v integrins is ␣ v ␤ 3 in these conditions ( Figure 5). …”
Section: Org Frommentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although Ca 2ϩ or Mg 2ϩ are required for ligand binding to integrins, neither by themselves activate integrins, whereas Mn 2ϩ , at millimolar concentrations, induces integrin-mediated cell adhesion, 4,9,31,32 binding of isolated integrins to immobilized ligands, 12,33,34 and binding of soluble ligands to integrins on cell surfaces. [35][36][37] The crystal structure of the extracellular portion of the integrin ␣v␤3 revealed that it contains 8 divalent cation-binding sites. 14 Four sites were located in the ␤-propeller domain of ␣v, 1 at the ␣ subunit genu (knee), and 3 in the ␤3 ␤A domain.…”
Section: Discussionmentioning
confidence: 99%
“…Mac-1 (CD11b/CD18) and ␣ V ␤ 3 (CD51/CD61) are two integrins expressed by neutrophils known to bind fibrinogen (48,49). To ‫ء‬ , p Ͻ 0.01, Student's t test (S100A8/A9 in both chambers vs S100A8/A9 in lower chamber only).…”
Section: Mrp-stimulated Neutrophil Adhesion To Fibrinogen Is Mediatedmentioning
confidence: 99%